Interviews, Disclosures, and Misperceptions: Autistic Adults’ Perspectives on Employment Related Challenges - Sarrett, Jennifer (Disability Studies Quarterly, 2017)
As increasing numbers of autistic adults are seeking and gaining employment, the experiences of autistic adults in the workplace is critical to consider. Autistic adults encounter a range of challenges in obtaining and keeping employment and often report a range of negative experiences in the workplace. The current research reports the results from a large, national exploratory study on the experiences of autistic adults in the workplace as well as their thoughts on how to improve these experiences for the autism community. In particular, participants reported challenges with the interviewing process, which requires very specific and consistent social behaviors, as well as with feeling comfortable disclosing one's autistic status at work. These challenges are often connected with public misperceptions about autism. The article discusses these challenges as well as strategies to improve autism-related understanding and awareness in the workplace. This work is critical to conversations about diversity in the workplace.